Recognizing other subjects : feminist pastoral theology and the challenge of identity - Lassiter, Katharine Eleanor, 1979- (The Lutterworth Press, 2016)
An interdisciplinary study that draws upon feminism and social theory to develop a theology of pastoral care that emphasises the importance of recognition for human well-being.